BRAF Signaling Inhibition in Glioblastoma: Which Clinical Perspectives? - Bouchè, Victoria; Aldegheri, Giovanni; Donofrio, Carmine Antonio; Fioravanti, Antonio; Roberts-Thomson, Samuel; Fox, Stephen B.; Schettini, Francesco; Generali, Daniele (Frontiers in Oncology, 2021)
IDH-wild type (wt) glioblastoma (GB) accounts for approximately 90% of all GB and has a poor outcome. Surgery and adjuvant therapy with temozolomide and radiotherapy is the main therapeutic approach. Unfortunately, after relapse and progression, which occurs in most cases, there are very limited therapeutic options available. BRAF which plays a role in the oncogenesis of several malignant tumors, is also involved in a small proportion of IDH-wt GB. Previous successes with anti-B-Raf targeted therapy in tumors with V600E BRAF mutation like melanoma, combined with the poor prognosis and paucity of therapeutic options for GB patients is leading to a growing interest in the potential efficacy of this approach. This review is thus focused on dissecting the state of the art and future perspectives on BRAF pathway inhibition in IDH-wt GB. Overall, clinical efficacy is mostly described within case reports and umbrella trials, with promising but still insufficient results to draw more definitive conclusions. Further studies are needed to better define the molecular and phenotypic features that predict for a favorable response to treatment. In addition, limitations of B-Raf-inhibitors, in monotherapy or in combination with other therapeutic partners, to penetrate the blood-brain barrier and the development of acquired resistance mechanisms responsible for tumor progression need to be addressed.